WALKING IT’S HEALTH, AN ACTIVITY FOR ALL AND ITS BENEFITS - Abdelkrim Ferguen; Karim Labane; Mohamed Riadh Fahssi (Sport Scientific And Practical Aspects, 2025)
Man has been walking for millennia; this physicalactivity is naturally an inalienable right of every living being. It is practised "Without knowing, more or less well, more or less quickly and more or less elegantly. But whoever does not practise it becomes disabled." F. Jenevein (1982) It is a vital activity of man, which deserves a deep study to promote it and finally meet the vital needs of man.Therapeutically, walking, since ancient Greece, Hippocrates considered it as the best remedy for humans. It prevents some of the most knowndiseases nowadays, such as blood pressure, blood sugar, osteoporosis, stroke, etc. This physical activity is an excellent antidote, it also helps keep fit, maintains joint flexibility by strengthening the bones. It also promotes the fight against stress.However, with the evolution of societies, the technological development of means of transport, the advent of the Internet where the purchases are made at home, this activity is practiced less and less. This therefore has influenced our life habits while reducing physical effort, especially walking. Indeed, we cannot turn back the clock, or reject all of these new technologies, how to insert this vital physical activity in our daily lives to maintain our well-being? How to properly practice walking to take advantage of its benefits?